Forage yield of some legumes in monoculture and mixtures under irrigation in central Sudan - Sid Ahmed, Nasreldein; Gangi, A.S; Ibrahim, A.E.S; Mohamed, I. E. (Gezira Journal of Agricultural Science, 2017)
The study was conducted during summer, autumn and winter seasons of 2014/15 and 2015/16 at the experimental farm of the Faculty of Agricultural Sciences, University of Gezira, Wad Medani, Sudan, to investigate the effect of mixing on forage yield of selected three legumes namely: cowpea (CP), black-eyed bean (BB) and lablab bean (LB) and their mixtures with three selected grasses, Sudan grass (SG), maize (MZ) and forage sorghum (Abu70). Legumes were grown in pure stand and mixed with grasses in 1:1 and 1:2 ratios. Treatment combinations were arranged in a randomized complete block design (RCBD) with four replications. The results showed that mixing significantly increased plant fresh weight, LAI, and fresh forage yield during most seasons and decreased number of branches per plant during different seasons. Land equivalent ratio mostly was greater than one. Based on the results of this study to obtain high forage yield, it was recommended to use seed combinations of 30 kg seeds/ha LB + 30 kg seed/ha MZ during autumn and winter and 30 kg seeds/ha BB + 30 kg seed/ha SG during summer season.     نفذت هذه الدراسة خلال صيف، خريف وشتاء 2014/2015 و2015/2016 بالمزرعة التجريبية لكلية العلوم الزراعية، جامعة الجزيرة، السودان. تهدف هذه الدراسة لتقييم أثر الخلط علي إنتاجية المحاصيل البقولية المختارة وهي اللوبيا الحلو واللوبيا البيضاء واللوبيا العفن ومخاليطها مع المحاصيل النجيلية حشيشة السودان، أبوسبعين والذرة الشامية تحت ظروف الري في أواسط السودان. زرعت المحاصيل البقولية منفرده وفي مخاليط بنسبة 1 : 1 و 1 : 2. تم استخدام تصميم القطاعات العشوائية الكاملة بأربعة مكررات. الخلط أدى إلى زيادة معنوية لكل من  وزن النبات الرطب، دليل مساحة الأوراق وإنتاجية العلف الأخضر خلال معظم المواسم بينما أدى الخلط إلى نقصان عدد الأفرع في مختلف المواسم. كانت قيم نسبة مكافئ الأرض في أغلب المواسم  أعلى من الواحد الصحيح. بناءً على نتائج هذه الدراسة ولتحقيق إنتاجية أعلاف عالية نوصي بزراعة المحاصيل البقولية في مخاليط بنسبة خلط 30 كجم بذور/هكتار لوبيا عفن + 30 كجم بذور/هكتار ذرة شامية خلال فصلي الخريف والشتاء وبنسبة 30 كجم بذور/هكتار لوبيا حلو + 30 كجم بذور/هكتار حشيشة السودان خلال فصل الصيف.